2015
DOI: 10.1177/0730888415618728
|View full text |Cite
|
Sign up to set email alerts
|

Persistence Is Cultural

Abstract: Why does sex segregation in professional occupations persist? Arguing that the cultures and practices of professional socialization serve to perpetuate this segregation, we examine the case of engineering. Using interview and diary entry data following students from college entry to graduation, we show how socialization leads women to develop less confidence that they will "fit" into the culture of engineering. We identify three processes that produce these cultural mismatches: orientation to engineering at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 43 publications
2
65
1
1
Order By: Relevance
“…Some businesses have attempted to increase diversity at work by encouraging the formation of affinity groups, which are typically promoted for workers who have experienced inequalities (e.g., women, people of color, and queer employees) in their work sites (Seron, Silbey, Cech, & Rubineau, 2016;Williams, Kilanski, & Muller, 2014). Affinity groups purportedly offset the advantages that men accrue from informal networking.…”
Section: The Devaluation Of Women's Relationships With Other Women mentioning
confidence: 99%
“…Some businesses have attempted to increase diversity at work by encouraging the formation of affinity groups, which are typically promoted for workers who have experienced inequalities (e.g., women, people of color, and queer employees) in their work sites (Seron, Silbey, Cech, & Rubineau, 2016;Williams, Kilanski, & Muller, 2014). Affinity groups purportedly offset the advantages that men accrue from informal networking.…”
Section: The Devaluation Of Women's Relationships With Other Women mentioning
confidence: 99%
“…Nevertheless, gender advantage and disadvantage are very much intertwined with age, generation, and the life course. For example, research has suggested that differences between men and women become particularly salient during key life course transitions, such as first entry into professional employment (Seron, Silbey, Cech & Rubineau, 2016), or during child-bearing years (Ranson, 2005;Demaiter & Adams, 2009). Moreover, generational differences are evident.…”
Section: Resultsmentioning
confidence: 99%
“…In Western culture, powerful, culturally gendered disciplinary practices produce docile, feminine bodies: acceptable social positions for women often include displays of "frailty, fear, and incompetence" (Goffman, 1977, p. 312), and these practices become even more pronounced, and reinforced, in the specific institutional context of STEM. Studies have strongly suggested that institutions and their agents, including STEM instructors, are a major force in the construction and transmission of traditional binary and heteronormative narratives of gender (e.g., Faulkner, 2000;Foor, Walden, & Trytten, 2007;Ong, 2005;Seron, Silbey, Cech, & Rubineau, 2016).…”
Section: Epistemological and Methodological Frameworkmentioning
confidence: 99%